The Bronx Nobody Knows : An Urban Walking Guide - Helmreich, William B. (Book collections on Project MUSE., 2023)
"For his award-winning book The New York Nobody Knows, which Princeton published in 2013, Bill Helmreich walked every block in New York City, around 6,000 miles. Then, he re-walked the city to research one-of-a-kind walking guides for general readers for each borough, uncovering the unusual and the unknown in New York City's neighborhoods. Bill Helmreich has taken readers through the ever-changing neighborhoods of Brooklyn, bustling Manhattan, vibrant Queens, and now in this installment, the Bronx, a borough his describes as filled with hope, history, beauty, and a strong sense of community. Helmreich provides a fascinating, detailed overview of the borough, highlighting major attractions like Yankee Stadium and the Bronx Museum of the Arts as well as architectural places of interest, like the Art Deco building at 888 Grand Concourse and the Concourse Plaza Hotel, once a luxury hotel in the Bronx that is now a senior citizens' residence. The Bronx Nobody Knows, like the previous guidebooks, is organized by neighborhood, and Helmreich delivers a personal and entertaining account of his travels as he interacts with locals and captures the heart of the borough"--